2018
DOI: 10.4103/jnrp.jnrp_308_17
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Preoperative ACTH/Cortisol Ratio for the Diagnosis and Prognosis of Cushing's Disease

Abstract: Purpose:Cushing's syndrome (CS) is a rare disease having diagnostic difficulties. Many diagnostic tests have been defined but none of these are diagnostic alone. Determination of the cause is another problem which sometimes requires more sophisticated and invasive procedures. Therefore, we aimed to evaluate the utility of pretreatment plasma adrenocorticotropic hormone (ACTH)/cortisol ratios in patients with confirmed endogenous CS for the diagnosis and differential diagnosis of CS.Materials and Methods:This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…Adrenocorticotropin/cortisol ratio was not previously evaluated in patients with psoriasis, but has been reported in other medical problems, such as the Cushing syndrome diagnostic test, viral infections, sepsis and psychoneurological studies [8][9][10][11]. Our analysis showed that ACTH/cortisol ratio correlates with the severity of psoriasis and can be possibly utilized as a biochemical marker of disease severity.…”
Section: Discussionmentioning
confidence: 73%
“…Adrenocorticotropin/cortisol ratio was not previously evaluated in patients with psoriasis, but has been reported in other medical problems, such as the Cushing syndrome diagnostic test, viral infections, sepsis and psychoneurological studies [8][9][10][11]. Our analysis showed that ACTH/cortisol ratio correlates with the severity of psoriasis and can be possibly utilized as a biochemical marker of disease severity.…”
Section: Discussionmentioning
confidence: 73%
“…As shown in Figure 1, the difference in median cortisol /ACTH ratio is more prominent than in the others. Using the ratio of cortisol/ACTH in the diagnosis of primary hypoadrenalism and/or Cushing's disease is suggested by some investigators (17,18). So, using this ratio in future similar studies of COVID-19 infected patients would add more information on the effect of this disease on the hypothalamic-adrenocortical axis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, preoperative ACTH and ACTH/cortisol ratio were significantly higher in patients who experienced recurrence as compared to patients with sustained remission (43). Conversely, in another study all postoperative patients who later experienced recurrence had an ACTH value >20 ng/l and all those with sustained remission had <20 ng/l, with a statistically significant difference (44).…”
Section: Adrenocorticotropic Hormone Levelsmentioning
confidence: 90%
“…The role of ACTH in diagnosing either remission or recurrence is controversial. Adrenocorticotropic hormone has been studied as a predictor for remission and prognosis of recurrence following TSS for CD, either measured before treatment (42, 43), perioperatively (44), or during the immediate postoperative period (26, 45). These studies were performed with ACTH levels alone, in conjunction with dehydroepiandrosterone (DHEA) and DHEA sulfate (DHEAS), ACTH to cortisol ratio, or ACTH following suppression with betamethasone.…”
Section: Adrenocorticotropic Hormone Levelsmentioning
confidence: 99%